Unveiling the redox control of plant reproductive development during abiotic stress - Zinta, Gaurav; Khan, Asif; AbdElgawad, Hamada; Verma, Vipasha; Srivastava, Ashish Kumar (Frontiers in plant science, 2016)
Plants being sessile in nature are often challenged to various abiotic stresses including temperature fluctuations, water supply, salinity, and nutrient availability. Exposure of plants to such environmental perturbations result in the formation of reactive oxygen species (ROS) in cells. To scavenge ROS, enzymatic and molecular antioxidants are produced at a cellular level. ROS act as a signaling entity at lower concentrations maintaining normal growth and development, but if their levels increase beyond certain threshold, they produce toxic effects in plants. Some developmental stages, such as development of reproductive organs are more sensitive to abiotic stress than other stages of growth. As success of plant reproductive development is directly correlated with grain yield, stresses coinciding with reproductive phase results in the higher yield losses. In this article, we summarize the redox control of plant reproductive development, and elaborate how redox homeostasis is compromised during abiotic stress exposure. We highlight why more emphasis should be given to understand redox control of plant reproductive organ development during abiotic stress exposure96to engineer crops with better crop yield. We specifically discuss the role of ROS as a signaling molecule and its cross-talk with other signaling molecules such as hormones and sugars.
Gesehen am 12.10.2021